Chronic Critical Illness and the Persistent Inflammation, Immunosuppression, and Catabolism Syndrome - Hawkins, Russell B.; Raymond, Steven L.; Stortz, Julie A.; Horiguchi, Hiroyuki; Brakenridge, Scott C.; Gardner, Anna; Efron, Philip A.; Bihorac, Azra; Segal, Mark; Moore, Frederick A.; Moldawer, Lyle L. (Frontiers in Immunology, 2018)
Dysregulated host immune responses to infection often occur, leading to sepsis, multiple organ failure, and death. Some patients rapidly recover from sepsis, but many develop chronic critical illness (CCI), a debilitating condition that impacts functional outcomes and long-term survival. The ‘Persistent Inflammation, Immunosuppression, and Catabolism Syndrome’ (PICS) has been postulated as the underlying pathophysiology of CCI. We propose that PICS is initiated by an early genomic and cytokine storm in response to microbial invasion during the early phase of sepsis. However, once source control, antimicrobial coverage, and supportive therapies have been initiated, we propose that the persistent inflammation in patients developing CCI is a result of ongoing endogenous alarmin release from damaged organs and loss of muscle mass. This ongoing alarmin and danger-associated molecular pattern (DAMP) signaling causes chronic inflammation and a shift in bone marrow stem cell production towards myeloid cells, contributing to chronic anemia and lymphopenia. We propose that therapeutic interventions must target the chronic organ injury and lean tissue wasting that contribute to the release of endogenous alarmins and the expansion and deposition of myeloid progenitors that are responsible for the propagation and persistence of CCI.